An Insight of Molecular Twisting of Coumarin Dyes. Issue 30 (13th August 2020) - Debnath, Tushar; Ghosh, Hirendra N.
Abstract: This article highlights the recent understanding of twisted intramolecular charge transfer state (TICT) of coumarin dyes on TiO2 and Au NP surface. The natural origin of coumarin dye in several plants makes it attractive to solar cell and fluorescence sensing applications. Two different classes of D‐π‐A coumarin dyes, having cyano‐acrylic acid as acceptor and 7‐amino moiety as a donor, have been chosen: one of them, having 7‐amino moiety in the ring, shows only intramolecular charge transfer (ICT) states in the excited state. While due to twisting of the free 7‐amino moiety, the second class of coumarin shows both ICT and TICT states in their photo‐excited states in the polar environment, in the form of a strong dual‐fluorescence. On TiO2 surface such coumarin dyes found to couple with carboxylic moiety, however on Au NP surface they bind with amino moiety. As a result, on TiO2 surface, the 7‐amino moiety is free to rotate, thus exhibiting TICT state which is a charge‐separated state and leads to higher electron injection yield for the second class of coumarins. The applicability of such twisted conformers of coumarin molecules in the solar cell has been demonstrated. Furthermore, due to molecular coupling with the 7‐amino moiety on Au NP surface, a restriction imposed on the molecular twisting of the free 7‐amino group. This constrains the formation of the TICT state for the second class of coumarins on the Au NP surface. Such ICT‐TICT fluorescence modulation character of the coumarin dyes may lead them to use for fluorescence sensing application, which is also demonstrated to detect specific ions and biomolecules. Thus the present review acmes very fundamental photophysical properties of coumarin dyes based on their molecular twisting on different solvents, semiconductors, and metal nanoparticles which have great consequences of real life applications. Abstract : The recent understandings of twisted intramolecular charge transfer state of coumarin dyes on TiO2 and Au nanoparticle surface have been highlighted in terms of ultrafast pump‐probe and fluorescence spectroscopy. The present review discussed the fundamental prospects of the structural behavior of coumarin dyes in different solvent medium, on semiconductor and metal nanoparticle surface which has tremendous implications in biological application, sensing and solar energy conversion.